PEMBUATAN KOMPOS TPA GUNUNG TUGEL - Susatyo & Chrisna Adhi Pramono & Pudyawardhana (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2007)
Abstract Garbage problems which often emerge is its difficult procure space for the Place Of Exile Of irrigate the (TPA), for a while at other side arise the garbage will increase in line with its resident growth.Method composting conducted effectively in TPA of Gunung Tugel will get the double benefit that is represent the efficient and effective step lessen the garbage volume in TPA of Gunung Tugel at one blow provide the organic manure which is good for crop and agriculture area.Method composting conducted consisted of the method, that are: composting Aerobe by Aerator, composting Anaerobe, and composting Aerobe of Non Aerator. From 3 conducted method, composting Anaerobe yield the compost production which is the more amount. Keyword: Compost, TPA of GunungTugel.